Religiosity and conflict handling styles: a study of a Muslim community - Azim, Mohammad Tahlil (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
This is a pioneering study to address the Islamic view of conflict and the preference of using conflict handing styles by the Devotee Muslims in Saudi Arabia. Independent sample T-test and paired T-test were run using SPSS version 16.0. The study reveals that there is a striking disparity between the Islamic directives and the preference of the self-claimed devotee Muslims. The prohibited dominating style turns out to be the second most preferred style whereas the most encouraged obliging style is observed to be the second least preferred style for the devotee Muslims. It indicates that the selfclaimed devotee Muslims have a lack of knowledge or comprehension about the breadth of Islam which implies that the Islamic scholars and the community leaders should emphasize on the totality of Islam through speeches, actions, and education. The study suggests that in-depth studies are required to explore the psychic makeup of Muslims as regards worship vis-a-vis interpersonal relationships.